The challenge of reforming a 'voter-friendly' electoral system: the debates over Ireland's single transferable vote. Issue 2 (3rd April 2017) - Farrell, David M.; Suiter, Jane; Harris, Clodagh
ABSTRACT: In the 2011 Irish general election, held in the midst of the economic crisis, electoral reform was catapulted to the top of the agenda, with all of the political parties including proposals for electoral reform in their manifestos. The matter was subsequently given to the Irish Constitutional Convention to discuss. The Convention recommended keeping a modified version of the existing single transferable vote electoral system. This article reviews the Irish debate, showing how for the most part the impetus for electoral reform came from the party leaderships. By contrast, mass public opinion on the issue was at best equivocal. A curious feature of the Irish debate was how arguably it was strategically misdirected, at least on the part of the mainstream parties: the reforms being promoted by the elite were more likely to have weakened the position of the established elite than to have strengthened it.